Blockchain technology to improve aerospace supply chains - Azian, Ibrahim; Fernando, Yudi (GBMR, 2023)
Purpose: Traceability in aerospace industries starts from procuring raw materials until the final assembly part of the aircraft. These processes involve different parts of the supply chain network, including raw material suppliers, manufacturers, and original equipment manufacturers. Due to the complexity of the supply chain process in aerospace industries, robust technologies such as blockchain technology are required to assist the supply chain process, which can lead to a company's operational excellence. The purpose of this research is to look at the existing practice of aerospace supply chain management and to identify the concerns and challenges that impede the use of blockchain technology in the management of aerospace supply chains. Design/methodology/approach: The qualitative research method was chosen, and an online interview was conducted to collect the information from informants. Findings: The findings reveal that the main challenges to blockchain adoption in the aerospace supply chain are cost and lack of knowledge. The outcome of this study presents significant theoretical and managerial implications and a deep understanding for practitioners who plan to develop blockchain technology in the aerospace supply chain. Research limitations/implications: The scope of this research is limited to the usage of blockchain in the aerospace industry's supply chain. It would be beneficial to broaden the scope of this research to include a comparison of the applications of blockchain technology in different industries. Practical implications: The successful implementation of blockchain technology in managing the aerospace supply chain can strengthen the manufacturing sector. It helps achieve sustainability by bringing transparency to the system and enhancing the market position. The emphasis on blockchain technology also helps take organizational practices toward achieving a competitive advantage by generating new operational excellence in the current complexity of the supply chain landscape. Originality/value: The results can be used as the framework to foresee the successful implementation of blockchain technology in managing an aerospace supply chain.